2022
DOI: 10.1038/s41396-022-01200-3
|View full text |Cite
|
Sign up to set email alerts
|

Biological manganese-dependent sulfide oxidation impacts elemental gradients in redox-stratified systems: indications from the Black Sea water column

Abstract: The reduction of manganese oxide with sulfide in aquatic redox-stratified systems was previously considered to be mainly chemical, but recent isolation of the Black Sea isolate Candidatus Sulfurimonas marisnigri strain SoZ1 suggests an important role for biological catalyzation. Here we provide evidence from laboratory experiments, field data, and modeling that the latter process has a strong impact on redox zonation in the Black Sea. High relative abundances of Sulfurimonas spp. across the redoxcline in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…One significant advantage of using lipid biomarkers for paleoenvironmental studies is their enduring preservation in the geological records. We first examined the relative abundance of H-GDGTs lipids in modern seas, alongside direct measurements of oxygen levels (40)(41)(42). The findings from the three sites in the Baltic Sea and Black Sea revealed that that H-GDGTs were much more prevalent in oxygen-deficient waters compared to oxic waters (Fig.…”
Section: H-gdgts a New Proxy For Ocean Deficiency In The Present And ...mentioning
confidence: 99%
“…One significant advantage of using lipid biomarkers for paleoenvironmental studies is their enduring preservation in the geological records. We first examined the relative abundance of H-GDGTs lipids in modern seas, alongside direct measurements of oxygen levels (40)(41)(42). The findings from the three sites in the Baltic Sea and Black Sea revealed that that H-GDGTs were much more prevalent in oxygen-deficient waters compared to oxic waters (Fig.…”
Section: H-gdgts a New Proxy For Ocean Deficiency In The Present And ...mentioning
confidence: 99%
“…The ability to oxidize glucose, in fact, was used to justify the proposition for the use of manganese oxide (Mn x O y ) nanoparticles as facilitators of the starvation of cancer cells [ 56 ]. Manganese, moreover, is an element that cycles across the ecosphere in its various redox states, such as in deep-sea basins, where dissolved Mn 2+ and intermediate Mn 3+ species are transported upward by diffusion until they are oxidized into Mn 4+ and form MnO 2 , which is solid and is transported downward due to gravity, toward anaerobic depths where it then undergoes reduction by sulfides and continues cycling [ 57 ]. This omnipresence of manganese redox processes and their essentiality for life provides strong support for choosing this element for incorporation into the smart drug delivery carrier investigated here.…”
Section: Introductionmentioning
confidence: 99%
“…The biologically catalyzed oxidation of HS - by Ca . S. marisnigri SoZ1 is faster than the abiotic oxidation of HS - with MnO 2 [ 14 ] and yields as the prominent end product, while elemental sulfur (S 0 ) accumulates in the abiotic reaction [ 13 , 15 , 16 ]. Combining the cellular abundance of Sulfurimonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…in the Black Sea redoxcline with rates of MnO 2 dependent HS - oxidation by Ca . S. marisnigri SoZ1 in a reaction diffusion model yielded adequate rates to counterbalance the HS - flux, resulting in the measured HS - concentration profile, in contrast to a pure abiotic reaction [ 14 ]. Hence, this process is likely to play a prominent role in HS - oxidation at the chemocline of the Black Sea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation